Japanese structure survey of radiation oncology in 2013. (10th July 2020) - Numasaki, Hodaka; Teshima, Teruki; Okuda, Yasuo; Ogawa, Kazuhiko; ,
ABSTRACT: This paper describes the ongoing structure of radiation oncology in Japan in terms of equipment, personnel, patient load and geographic distribution to identify and overcome any existing limitations. From December 2014 to July 2017, the Japanese Society for Radiation Oncology conducted a questionnaire based on the Japanese national structure survey of radiation oncology in 2013. Data were analyzed based on institutional stratification by the annual number of new patients treated with radiotherapy per institution. The estimated annual numbers of new and total (new plus repeat) patients treated with radiation were 216 000 and 257 000, respectively. Additionally, the estimated cancer incidence was 862 452 cases with 25.0% of all newly diagnosed patients being treated with radiation. The types and numbers of treatment devices actually used included linear accelerator (LINAC; n = 880), Gamma Knife ( n = 45), 60 Co remote afterloading system (RALS; n = 23) and 192 Ir RALS ( n = 128). The LINAC system used dual-energy functions in 675 units, 3D conformal radiotherapy functions in 785 and intensity-modulated radiotherapy (IMRT) functions in 494. There were 831 Japan Radiological Society/Japanese Society for Radiation Oncology-certified radiation oncologists, 1130.6 full-time equivalent (FTE) radiation oncologists, 2214.6 FTE radiotherapy technologists, 196.6 FTE medical physicists, 183.8 FTE radiotherapy quality managers and 856.7 FTE nurses. The frequency of IMRT use significantly increased during this time. In conclusion, the Japanese structure of radiation oncology has clearly improved in terms of equipment and utility although there was a shortage of personnel in 2013.